The Alteration of Young Boxers' Athletic and Special Physical Fitness during the First Year of their Physical Training - Algirdas Čepulėnas; Vitalijus Subačius; Vidas Bružas; Pranas Mockus (Lithuanian Sports University, 2018)
The goal of this study was to analyze the alteration of young boxers' athletic and special physical fitness during the annual cycle of their initial training. Research methods: literature review, experiment, testing, comparative analysis, and mathematical statistics. The sample consisted of 14 persons, who were training boxing for one year. The average age of the boxers was 14.9 ± 0.6 years. The duration of the experiment was 10 months (from September till June). The young boxers were training 1-1.5 hours 5 times per week according to the program which was made for them. The training program of one alternative was applied in the experiment. The initial training program contained 24.6% of athletic training, 27.6% of specialphysical training, 28.5% of technical training, and 19.3% of tactical training. The testing of the boxers was performed three times: the first testing was in October, the second one - in February, and the third one - in June. The following training means were used for the young boxers' athletic training program: physical exercises on the special equipment, exercises with partner, exercises with weights (dumbbells), short distance running, point-to-point running, various jumps, throwing of the stuffed ball, various games. The main means for the young boxers' special training were imitation exercises, exercises with a rope and lawn tennis balls, exercises at the boxing bags, straight and side thrusts to the boxing bag, defense exercises, thrust imitation using the dumbbells and the stuffed balls. During the annual cycle of the initial training there was a minor alteration in the indexes of the young boxers' body composition: their height, body weight and Ketle index increased (p < 0.05), while the amount of the fat (%) within the body and the body weight index changed very little (p > 0.05). The strength of the sportsmen's right hand palm was always bigger than the strength of the left hand palm. The boxers' athletic and special physical fitness improved (p < 0.05) during one year of their initial training. The boxers' speed, explosive strength, anaerobic glicolitic endurance, hand strength endurance and flexibility indexes increased significantly (p < 0.05). The strength of the single side thrusts with the front hand to the boxing bag increased from 106.3 ± 7.5 kg to 127.6 ± 8.15 kg (p < 0,05). The strength of the single thrusts with the straight hand increased from 135.2 ± 7.43 kg to 158.5 ± 6.74 kg (p < 0.05). The amount of the thrusts of the examined boxers during the period of 8 sec increased (p < 0.05) in each testing period and at the end of the experiment, the average amount of the boxers' thrusts in 8 s was 43.5 ± 2.9. The training program, determined for one alternative experiment significantly improved the preparation of young boxers and did not harm their health. During the annual preparation cycle the athletic and special physical fitness of the boxers improved. The implementation of this experimental program made a positive influence on the alteration of the body composition indices of the young boxers. Keywords: athletic training, special physical training, boxing bag, energy input, total energy, total strength